Adequacy of Healthcare by Insurance Type in Traumatic Brain Injury Patients. (December 2022) - Smith, Drew; Santiago, Juan; Castro, Grettel; de la Vega, Pura Rodriguez; Barengo, Noël C.
Traumatic brain injury (TBI) is a significant contributor to disability, especially among patients younger than 18 years old in the United States. While insurance is often needed to receive services, studies investigating whether TBI treatment adequacy is dependent on the insurance type are scant. Our objective was to determine whether private insurance in paediatric TBI patients is associated with a higher perceived adequacy of healthcare compared with non-private insurance. This was a cross-sectional study utilising secondary data collected from the National Survey of Children Health 2011/12. The main exposure of interest was the insurance status of children at the time of a TBI (private vs non-private). The study outcome was the perceived adequacy of healthcare, defined as having coverage needs that were usually or always met by insurance. Unadjusted and adjusted logistic regression analysis were used. After adjustments for the covariates, the odds of adequate healthcare among those with non-private insurance compared with those with private were not statistically significant (OR 1.49; 95% CI 0.87–2.55). This study implicates paediatric TBI patients do not believe they receive adequate healthcare independent of insurance status. Clinicians, policy makers, and researchers need to better evaluate and address this issue.